Analyze the Level of Driver Satisfaction with the Application Maxim Uses the Pieces Method - Andestian Wirayuda; Khana Wijaya; Jepri Yandi (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
In this era of globalization, Maxim is present in online transportation. This research aims to analyze driver satisfaction with the Maxim application using the PIECES method. The problem faced by drivers is complaints about the application features available in the Maxim application. Therefore, it is necessary to analyze driver satisfaction with the Maxim application, to find out the factors that influence user satisfaction. The PIECES method is used to measure driver satisfaction with the Maxim application using 6 variables, namely performance, information, economy, control & security, efficiency, service. The results of the Validity Test using SPSS are declared valid from the r table value, namely 0.150. The results of the Reliability Test value for all data are greater than the r table value, namely 0.150. Based on the results of Likert scale calculations for all variables, the average is 84.7%.